The Efficacy and Cost-Effectiveness of Cell Saver Use in Instrumented Posterior Correction and Fusion Surgery for Scoliosis in School-Aged Children and Adolescents - Miao, Yu-Liang; Ma, Hua-Song; Guo, Wen-Zhi; Wu, Ji-Gong; Liu, Yan; Shi, Wen-Zhu; Wang, Xiao-Ping; Mi, Wei-Dong; Fang, Wei-Wu (PloS one, 2014)
Posterior spinal instrumentation and fusion surgery in school-aged children and adolescents is associated with the potential for massive intraoperative blood loss, which requires significant allogeneic blood transfusion. Until now, the intraoperative use of the cell saver has been extensively adopted; however, its efficacy and cost-effectiveness have not been well established. Therefore, the aim of this study is to determine the efficacy and cost-effectiveness of intraoperative cell saver use. This study was a single-center, retrospective study of 247 school-aged and adolescent patients who underwent posterior spinal instrumentation and fusion surgery between August 2007 and June 2013. A cell saver was used intraoperatively in 67 patients and was not used in 180 patients. Matched case-control pairs were selected using a propensity score to balance potential confounders in baseline characteristics. Allogeneic red blood cell (RBC) and plasma transfusions as well as blood transfusion costs were analyzed. The propensity score matching produced 60 matched pairs. Compared to the control group, the cell saver group had significantly fewer intraoperative allogeneic RBC transfusions (P = 0.012). However, when the combined postoperative and total perioperative periods were evaluated for the use of allogeneic RBC transfusion, no significant differences were observed between the two groups (P = 0.813 and P = 0.101, respectively). With regard to the total cost of perioperative transfusion of all blood products (RBC and plasma), costs for the control group were slightly lower than those of the cell saver group, but this variance did not reach statistical significance (P = 0.095). The use of the cell saver in posterior spinal instrumentation and fusion surgery in school-aged children and adolescents was able to decrease the amount of intraoperative allogeneic RBC transfusion but failed to decrease total perioperative allogeneic RBC transfusion. Moreover, the use of the cell saver was not cost-effective.